Flyback PFC With a Series-Pass Module in Cascode Structure for Input Current Shaping - Tung, Chung-Pui; Wang, Ke-Wei; Ho, Ka-Wai; Chow, Jeff Po-Wa; Fan, John Wing-To; Chan, Wan-Tim; Chung, Henry Shu-Hung (IEEE transactions on power electronics, 2019)
A flyback power factor corrector (PFC) using a series-pass module (SPM) to shape its input current is presented. The input current is profiled by the SPM with its waveform controlled to be in the same wave shape and phase with the supply voltage and its magnitude controlled to regulate the output voltage. The SPM is constructed by two series-connected power semiconductor devices in a cascode structure. One of them is a high-voltage device of low on -state resistance for sharing major voltage stress, while the other one is a low-voltage device with high-output impedance for profiling the current through the SPM. The SPM has a local control for clamping the voltage across the low-voltage device. Such arrangement allows the PFC to exhibit lower total input current harmonic distortion than that using a single high-voltage series-pass device. To minimize power loss, the operating point of the low-voltage device is regulated around the boundary between its high-gain and fully turn- on operating region by adjusting the duty cycle of the main switch in the flyback converter. A 100-W 85-265-Vac/36-Vdc prototype has been built and evaluated. The conducted electromagnetic interference under different supply voltages will also be given.